Analysis of Willingness to Pay Integrated Waste Management - Bakara, Tionarta; Bowo, Prasetyo Ari (Universitas Negeri Semarang, 2019)
Waste volume in Semarang City increases every year. Local Regulation Number 6 Year 2012 forces households to reduce waste through 3R. 83% pre-survey citizens in West Semarang District have not done it yet. It needs an improvement on waste management. The purpose of this research is to know the citizen’s willingness to pay rate of West Semarang District on waste management improvement and to analyze the factors affecting willingness to pay. The data used in this research is Primary Data. The population in this research is 100 households in West Semarang District. Data collection method is using interview. Data analysis method is using Contingent Valuation Method and multiple linear regression. The result shows that 68 respondents are willing to pay and 32 respondents are not. The amount of willingness to pay is Rp16.838. Influencing factors of willingness to pay are education level and staying duration. The recommendation of this research is the higher willingness to pay should be followed by better management service. Citizens can improve willingness to pay by having higher education level so that they realize the importance of maintaining environment. To increase willingness to pay, the higher family members the more they should have a good knowledge so that their perception about the payment based on head of the family will decrease. Volume sampah di Kota Semarang meningkat setiap tahun. Peraturan Daerah Nomor 6 Tahun 2012 memaksa rumah tangga untuk mengurangi limbah melalui 3R. 83% warga pra-survei di Kabupaten Semarang Barat belum melakukannya. Perlu perbaikan dalam pengelolaan limbah. Tujuan dari penelitian ini adalah untuk mengetahui kesediaan warga untuk membayar tarif Kabupaten Semarang Barat pada peningkatan pengelolaan limbah dan untuk menganalisis faktor-faktor yang mempengaruhi kesediaan untuk membayar. Data yang digunakan dalam penelitian ini adalah Data Primer. Populasi dalam penelitian ini adalah 100 rumah tangga di Kabupaten Semarang Barat. Metode pengumpulan data menggunakan wawancara. Metode analisis data menggunakan Metode Contingent Valuation dan regresi linier berganda. Hasilnya menunjukkan bahwa 68 responden bersedia membayar dan 32 responden tidak. Jumlah kemauan untuk membayar adalah Rp16.838. Faktor-faktor yang mempengaruhi kemauan untuk membayar adalah tingkat pendidikan dan durasi tinggal. Rekomendasi dari penelitian ini adalah semakin tinggi kesediaan untuk membayar harus diikuti oleh layanan manajemen yang lebih baik. Warga dapat meningkatkan kemauan untuk membayar dengan memiliki tingkat pendidikan yang lebih tinggi sehingga mereka menyadari pentingnya menjaga lingkungan. Untuk meningkatkan kemauan membayar, semakin tinggi anggota keluarga semakin mereka harus memiliki pengetahuan yang baik sehingga persepsi mereka tentang pembayaran berdasarkan kepala keluarga akan berkurang.